Strategies for Utilizing Fiction Literature as an Antidote to Radical Islamic Understanding among Students of UIN KHAS Jember - Ardianta, Shidiq; Arifin, Zinal (Yayasan Azhar Amanaa Yogyakarta, 2022)
This research was motivated by the desire to describe efforts to prevent radical Islamic understanding that developed among students by utilizing literary reading materials. The research that will be conducted is a qualitative descriptive research based on field research. The research focuses on “the strategy of using fiction genre literature as an antidote to radical Islamic understanding among students of UIN KHAS Jember. There are several research focuses that will be examined in this study. First, what fictions contain the teachings of kaffah Islam and can be used as media to counter radical Islam at UIN KHAS Jember? Second, how to implement the use of fiction in an effort to counteract radical Islamic teachings among students of UIN KHAS Jember? The results of this study are as follows. First, fictions containing kaffah Islamic teachings include Gus Jafar, Ayat-Ayat Cinta, Teroris, Kang Soleh, Robohnya Surau Kami. Second, the implementation of the use of fiction at UIN KHAS Jember in the form of short stories and novels is maximized in the form of lecture assignments. Lecturers give directions to students to read and study selected fiction. Lecturers provide assistance and provide explanations about fictional mandates. This method is effective in strengthening the understanding of moderate Islam for students.